RANCANGAN MEDIA LEAFLET BUDIDAYA JAMUR TIRAM PUTIH (Pleurotus ostreatus) PADA MATERI BIOTEKNOLOGI KONVENSIONAL UNTUK BIOLOGI SMA KELAS XII (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to determine the potential of leaflet design on conventional biotechnology materials for learning Biology in high school class XII. This research was conducted at the Binawidya Campus, Riau University in September - November 2019. The design of this study used the ADDIE model, namely the analysis (analyze) and design (design) stages. This study uses an experimental method with a quantitative descriptive type of research. Based on the results of the potential analysis, the results obtained from the production of white oyster mushroom cultivation can be used as leaflet designs on conventional biotechnology material for class XII that are by curriculum analysis, namely KD 3.10 and 4.10.Key Words: Leaflet, Biotechnology material, White Oyster Mushroom.